2016
DOI: 10.1093/europace/euw310
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis depth and conduction disturbances after last generation balloon-expandable transcatheter aortic valve implantation

Abstract: A low AVR is associated to higher ΔPR and PPMI rates. The correlation between LVOT prosthesis depth with ΔPR and higher PPMI rate suggests the need of a careful S3-THV implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…97 For each millimeter of increase in the depth of the valve at the septal side, the risk of PPMI increased 1.41 times. 98 This metaanalysis pooled five articles enrolling 854 patients including 151 cases with PPMI after TAVR and 703 cases without PPMI after TAVR (Table 8) and compared the average depth between patients with and without PPMI after TAVR. The depth was defined as the lowest site of annular plane to the distal site of valve device.…”
Section: The Influence Of Implantation Depth On Post-tavr Ppmi Riskmentioning
confidence: 99%
“…97 For each millimeter of increase in the depth of the valve at the septal side, the risk of PPMI increased 1.41 times. 98 This metaanalysis pooled five articles enrolling 854 patients including 151 cases with PPMI after TAVR and 703 cases without PPMI after TAVR (Table 8) and compared the average depth between patients with and without PPMI after TAVR. The depth was defined as the lowest site of annular plane to the distal site of valve device.…”
Section: The Influence Of Implantation Depth On Post-tavr Ppmi Riskmentioning
confidence: 99%
“…Our analysis confirmed that the ID and ΔMSID were independent predictors of new PMI after TAVR, as well as conventional predictors. Because of the proximity between the aortic valve and conduction system, deep prosthesis implantation is associated with an increased risk of conduction disturbance, and therefore, these factors have been reported as predictors of new PMI after TAVR 11,16–18 . The importance of ΔMSID might indicate that the current TAVR practice should focus not only on ID and MS length but also on the balance them.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the MS length using two methods as previously described by Hamdan et al 7 and Jilaihawi et al 8 In brief, Hamdan et al 7 measured the MS length as the distance between the aortic annulus and the top of the muscular septum using the non‐reformatted standard coronal plane view (defined as the “coronal view method”), whereas Jilaihawi et al 8 measured it using the perpendicular annular plane view (defined as “annular view method”) (Supporting Information: figure). The ID of the prosthesis was defined as the distance from the bottom of the non‐coronary cusp to the ventricular end of the valve stent frame in the final angiogram after valve implantation, based on the previous studies 8,11,12 . Using the parameters mentioned above, the differences between the MS length and the ID were calculated and defined as ΔMSID 7,8 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations